Current trends and future perspectives of stroke management through integrating health care team and nanodrug delivery strategy - Han, Xuelu; Qin, Yingxin; Mei, Chunli; Jiao, Feitong; Khademolqorani, Sanaz; Nooshin Banitaba, Seyedeh (Frontiers in Cellular Neuroscience, 2023)
Stroke is accounted as the second-most mortality and adult disability factor in worldwide, while causes the bleeding promptly and lifetime consequences. The employed functional recovery after stroke is highly variable, allowing to deliver proper interventions to the right stroke patient at a specific time. Accordingly, the multidisciplinary nursing team, and the administrated drugs are major key-building-blocks to enhance stroke treatment efficiency. Regarding the healthcare team, adequate continuum of care have been declared as an integral part of the treatment process from the pre-hospital, in-hospital, to acute post-discharge phases. As a curative perspective, drugs administration is also vital in surviving at the early step and reducing the probability of disabilities in later. In this regard, nanotechnology-based medicinal strategy is exorbitantly burgeoning. In this review, we have highlighted the effectiveness of current clinical care considered by nursing teams to treat stroke. Also, the advancement of drugs through synthesis of miniaturized nanodrug formations relating stroke treatment is remarked. Finally, the remained challenges toward standardizing the healthcare team and minimizing the nanodrugs downsides are discussed. The findings ensure that future works on normalizing the healthcare nursing teams integrated with artificial intelligence technology, as well as advancing the operative nanodrugs can provide value-based stroke cares.